Abnormal dentition in a boy with incontinentia pigmenti: case report. - H Afshar; M Daneshpazhooh; A Kiani; P Aref; Z Baniameri (Tehran University of Medical Sciences, 2012)
Incontinentia pigmenti (IP) is an X-linked dominant genodermatosis characterized by typical skin lesions along Blaschko's lines and associated with ocular, dental, nails, hair, skeletal, central nervous system and cardiovascular anomalies. We report a 5-year-old boy with cutaneous hyperpigmentation along Blaschko's lines, atrophic streaks, strabismus and mental retardation. He showed the characteristic abnormal dentition seen in IP as partial hypodontia, peg-shaped anterior teeth and un-erupted teeth. The expression of IP in boys is exceptional as the disease is lethal in males.